95 Long-term dual antiplatelet therapy after myocardial infarction in clinical practice: impact of nuisance bleeding on medication adherence. (8th December 2021) - Ratti, Gennaro; Di Tommaso, Cristina; Monda, Cinzia; Elettrico, Ciro; Ratti, Federica; Fulgione, Cosimo; Mallardo, Mario; Tammaro, Paolo
Abstract: Aims: Long-term treatment with ticagrelor 60 mg and low-dose aspirin are indicated after acute coronary syndrome (ACS) for the secondary prevention of atherothrombotic events in high-risk patients with a history of myocardial infarction of at least 1 year. Long-term dual antiplatelet therapy (DAPT) had a well tolerability and safety profile, but the risk of TIMI major bleeding was significantly increased. However e ven nonsignificant bleeding may be important because have an effect on quality of life and therefore may lead to treatment discontinuation. To understand the experiences of patients with long-term DAPT with ticagrelor 60 mg and low-dose aspirin and nuisance bleeding, and their impact of nuisance bleeding on medication adherence. Methods and results: We retrospectively reviewed aggregate data of 187 patients (155 M e 38 F) (mean age 63.8 ± 9 years) in follow-up after ACS with at least one high risk condition (multivessel disease, diabetes, GFR < 60 mL/min, history of prior myocardial infarction, age > 65 years) treated with ticagrelor 60 mg twice daily (after 90 mg twice daily for 12 months). The high risk groups were represented as follows: multivessel disease 105 pts (82%), diabetes 63 pts (33%), GFR< 60 mL/min 27 pts (14%), history of prior MI 33 pts (17%), and >65 year aged 85 pts (45%). The outpatient follow-up programme after hospitalization provides visits at day 30 after discharge and subsequently after 3 months, then continuing with 6-monthly checks. The intensity of bleeding was assessed according to the TIMI score. 1 Any overt bleeding event that did not meet the criteria of major and minor was defined 'minimal'. Treatment was withdrawn in seven patients: three cases showed atrial fibrillation and were placed on oral anticoagulant drugs, one developed intracranial bleeding. In three patients, a temporary withdrawal was due to surgery (one colon polyposis and two cases of bladder papilloma). Minimal bleedings (nasal, gingival, conjunctival, subcutaneous/dermal, rectal and urinary) were present in 31 patients, but were not a cause for discontinuation of therapy. However, 22 (70%) subjects had asked opinion on stop the therapy at the telephone consultation. We found that: (i) participants adhered to treatment when they believed long-term DAPT was important to health outcomes; (ii) those who experienced nuisance bleeding reported symptoms to be mild and manageable; (iii) participants' and their family's understanding of long-term DAPT risks and benefits, and their ability to manage symptoms, influenced medication adherence. Factors influencing long-term DAPT knowledge included access to medication counselling, engaging with information communicated during medication counselling, and access to timely, relevant and expert information and advice after discharge from hospital. Conclusions: All adverse events judged to be 'not serious' in trials may have an effect on quality of life and therefore may lead to treatment discontinuation. The need to educate the patient in order to improve adherence should therefore be emphasized. The authors underline the importance of careful outpatient follow-up and constant counselling in order to check out compliance and possible adverse effect of long term DAPT risks treatment.